Lider ve vizyon ilişkisi açısından dönüştürücü liderlik ve uygulamadan bir örnek - Alkan, Osman (My University, 2006)
LİDER VE VİZYON İLİŞKİSİ AÇISINDAN DÖNÜŞTÜRÜCÜ LİDERLİK VE UYGULAMADAN BİR ÖRNEK Liderlik, insanlık tarihinin her döneminde stratejik bir öneme sahip olmuştur. İnsanları bir amaca yöneltme ve bu amaç doğrultusunda örgütleyebilme becerisi liderliğin

tanımlarından biridir. Liderlik kavramı yaşanılan dönemin özelliklerinden etkilenen ve değişime uğrayabilen esnek bir yapıdadır. Günümüzde de güncel olarak değişimin meydan okumalarına karşın geliştirilen liderlik konsepti de “Dönüştürücü Liderlik’tir.” Dönüşümcü liderlik süreci genel liderlik teorilerinden farklı özellikler taşımakta, izleyenlerini değişime inandırmakta ve motive etmekte, onları farklı olarak yeniliğe ve değişime dönük olmalarını sağlamaktadır. Çünkü, değişim, günümüzdeki bütün sosyal yapılarını kökten değiştirmiştir. İşletmelerin yönetim biçimlerini, insanların ve toplumların davranışlarını, kültürlerini, talep ve ihtiyaçlarını da derinden etkilemiştir. Küreselleşen dünya da işletmeler hala değişmeden statükolarını devam ettirdikleri sürece yeni ve zorlayıcı bir piyasada var olmaları ve rakiplerine rekabet üstünlüğü sağlamalarının mümkün olmadığı açıktır. İşletmeleri hızlı ve esnek olmayan hantal yönetim biçimleri ile yönetmeye devam etmeleri durumunda yerlerini koruyamadıkları gibi gelecekte de var olmaları mümkün gözükmemektedir. Bu yeni yapıya uyumun geleneksel liderlik anlayışları ile sağlanmasının mümkün olmadığı ve değişim temelli bir liderlik anlayışının ortaya çıkmasının gerekli olduğu bir döneme girilmiştir. Bu yeni liderlik anlayışı dönüştürücü liderliktir. Bu liderlik stili sadece geleceği tahmin etmekle kalmaz geleceğe bir anlamda senaryosunu da yazarak nasıl gerçekleştirildiğini de planlar ve tasarlarlar. Bu tasarımı yaparken çalışanlarını da sorunların çözümünde farklı yöntemleri uygulamaları hususunda cesaretlendirir ve bunu hep yapmaları yönünde çalışanlarını teşvik ve telkinde bulunur. SUMMARY A SAMPLE FROM TRANSFORMATIONAL LEADERSHIP AND APPLICATION IN TERMS OF LEADER AND VISION RELATIOSHIP Leadership has always had strategic importance in every period of human history. Being able to direct people to a specific purpose and the ability of organizing the people for this purpose is one of the basic definitions of the leadership. Leadership concept is in a flexible structure which can be affected by the features of recent period and also it may change accordingly. Today, the developed leadership concept – despite the daily change – is the “Transformational Leadership”. Leadership undoubtedly has been important in each and every period but it has gained much more importance in today’s world which transformation has a significant and strategic feature. Transformation and its leadership period has different features than general leadership theories, and it makes the employee believe in change and it motivates them and also it differently makes them feel positive about innovation and change. Because the change has radically alterated all the social structures of today’s world. It has also deeply affected the management ways of the business administrations, the behaviours, cultures, demands and needs of the people and society’s. In the globalized world, as long as the business administrations maintain their status quo without any alteration, it is impossible for them to exist in a new and compelling market and to have a competitive advantage on their competitors. If they continue managing the business administrations by means of an inflexible management and slow management ways, they will not only be able to keep their places but also it seems that it is impossible fort hem to exist in the future. A new period has started that it is imposible to accommodate to the new structure by means of traditional leadership insights and it is necessary that a leadership which is based on change has to come out. This leadership style not only predicts the future but also it writes its scenario so that it plans and designs how it is carried out. While planning this, it also encourages its employee to apply different methods in the solution of the problems and it stimulates and inspires its employee to do this constantly. In this context, during the research, the transformational leadership features of the public and private university administrators have been examined and between these two groups, certain meaningful differences have been found out on behalf of public university administrators.
Keywords: Dönüştürücü Liderlik; Liderlik; Strateji_Yönetim; Vizyon